The Use of Ecological Region in Geography Teaching - (:unkn) unknown (MARMARA UNIV, 2017)
From 10 kilometres of ocean floor up about to 10 kilometres of atmosphere known as the feeding place of all living beings. This area is called as biosphere in world's layers. Ecology deals with living beings and their interactions with each other in this vertical 20 kilometres area. Currently, ecology gains in importance. Humans use soils to grow crops as they pollute the environment with industrial wastes for centuries, although water and the atmosphere are essential components of human sustainability. Ecology teaches us to live in harmony with the environment and humans should know that it is beneficial for humans to live sustainably in interactions with the environment in the long run. Regions is one of the core concepts in geography. Region is an area having common characteristics. These characteristics can be natural, human and cultural ones. Geographical region is a part of the earth specified by the natural, human and economic features of the earth. The criteria used to determine the geographical regions could be all these mentioned features. There is a principle in ecology like everything is related to everything else. That's way, it is related to geography too. There is no subject without a relation to geography. We do not have an intention to debate the region concept, quite the other way round we want to include ecological region into this concept. We wish to discuss the concept and usage of the ecological region considering the lack of awareness of this concept in geography. Because ecological region is not a region that is politically defined. Ecological region is a broader region containing especially all natural features.
Keywords: Geography; teaching; region; ecological region